Edukasi Rolling dan Areola Massage menggunakan Jitu Oil dengan Relaksasi Murottal Al-qur'an untuk pengeluaran ASI - Ningsih, Dewi Andariya; Andini, Dwi Margareta; Aisyah, Siti Rohmah Nur; Nurhidayati, Siti; Silaturrohmih, Silaturrohmih (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Lack of knowledge among breastfeeding mothers about the importance of smooth and adequate breast milk in mothers which can be done with Rolling and Areola massage using Jitu oil with relaxation of the Al-Qur'an murottal. The aim of this activity is to inform breastfeeding mothers about the benefits of massage therapy in helping to make breastfeeding a success. The location of the activity is in the working area of the Arjasa Community Health Center. This study involving up to 45 participants was carried out on breastfeeding mothers between March and May 2023. The implementation method was by contacting midwives, cadres and breastfeeding mothers in the local area, a time contract after which the breastfeeding mother filled in the pre-sheet, followed by counseling and mentoring. Lastly, the breastfeeding mother fills in the post sheet. After that, the results are recorded by the implementer. As a result, 77% of all breastfeeding mothers were able to feel the effects of massage with good results, so it can be concluded that this activity was successful and smooth, as seen from the enthusiasm and unity of all those involved in this activity.